Mentoring tertiary students from a secondary school incubator programme focusing on health careers: Findings from a New Zealand study. (10th October 2016) - Crawford, Ruth; Monson, Kathy; Searle, Judy
Abstract : Purpose: Developing the health workforce is an ongoing concern, especially in New Zealand, where Māori and Pasifika populations are under-represented. Programme Incubator (PI) was developed by a health provider to raise awareness of careers in the health sector. The purpose of this paper is to report on a study undertaken in a tertiary institution which involved tracking and mentoring students who had been engaged in PI, and mentoring them through their tertiary studies. Design/methodology/approach: In total, 40 students ( n =40) were recruited into the four year study, which involved a survey and participating in focus groups. Findings: PI was found to be an effective initiative of encouraging secondary students to enter a career in health, but more work is needed to facilitate students' choice of tertiary provider and academic programme. Within the tertiary sector, mentoring was found to be lacking. Originality/value: Group mentoring and peer mentoring are introduced to mitigate these concerns and provide students with the mentoring support they require.